Optimization of screening-level risk assessment and priority selection of emerging pollutants – The case of pharmaceuticals in European surface waters - Zhou, Shangbo; Di Paolo, Carolina; Wu, Xinda; Shao, Ying; Seiler, Thomas-Benjamin; Hollert, Henner (Environment international, 2019)
Pharmaceuticals in surface waters have raised significant concern in recent years for their potential environmental effects. This study identified that at present a total of 477 substances (including 66 metabolites and transformation products) have been analyzed in European surface waters. Around 60% (284) of these compounds belonging to 16 different therapeutic groups were positively detected in one or more of 33 European countries. To conveniently and effectively prioritize potential high-risk compounds, an optimized method that considers the frequency of concentrations above predicted no effects levels was developed on the basis of the traditional method, and it was then used to identify and screen candidate priority pollutants in European surface waters. The results proved the feasibility and advantages of the optimized method. Pharmaceuticals detected in European surface waters were classified into 5 categories (high, moderate, endurable, negligible and safe) depending on their potential environmental effects and the distribution of pharmaceuticals. Circa 9% (45 out of 477) analyzed compounds showed a potential environmental risk to aquatic ecosystems. Among these 45 compounds, 12 compounds were indicated to have high environmental risk in aquatic environments, while 17 and 7 compounds showed moderate and small-scale environmental risks, respectively. [Display omitted] •An optimized method was developed to identify and screen candidate priority pollutants in surface waters.•Different therapeutic groups were positively detected in many European countries.•45 compounds showed potential environmental risks in European surface waters.